On the motion of dayside auroras caused by a solar wind pressure pulse - Kozlovsky, A.; Safargaleev, V.; Østgaard, N.; Turunen, T.; Koustov, A.; Jussila, J.; Roldugin, A. (CCSD, 2005)
International audience Global ultraviolet auroral images from the IMAGE satellite were used to investigate the dynamics of the dayside auroral oval responding to a sudden impulse (SI) in the solar wind pressure. At the same time, the TV all-sky camera and the EISCAT radar on Svalbard (in the pre-noon sector) allowed for detailed investigation of the auroral forms and the ionospheric plasma flow. After the SI, new discrete auroral forms appeared in the poleward part of the auroral oval so that the middle of the dayside oval moved poleward from about 70° to about 73° of the AACGM latitude. This poleward shift first occurred in the 15 MLT sector, then similar shifts were observed in the MLT sectors located more westerly, and eventually the shift was seen in the 6 MLT sector. Thus, the auroral disturbance "propagated" westward (from 15 MLT to 6 MLT) at an apparent speed of the order of 7km/s. This motion of the middle of the auroral oval was caused by the redistribution of the luminosity within the oval and was not associated with the corresponding motion of the poleward boundary of the oval. The SI was followed by an increase in the northward plasma convection velocity. Individual auroral forms showed poleward progressions with velocities close to the velocity of the northward plasma convection. The observations indicate firstly a pressure disturbance propagation through the magnetosphere at a velocity of the order of 200km/s which is essentially slower than the velocity of the fast Alfvén (magnetosonic) wave, and secondly a potential (curl-free) electric field generation behind the front of the propagating disturbance, causing the motion of the auroras. We suggest a physical explanation for the slow propagation of the disturbance through the magnetosphere and a model for the electric field generation. Predictions of the model are supported by the global convection maps produced by the SuperDARN HF radars. Finally, the interchange instability and the eigenmode toroidal Alfvén oscillations are discussed as ...